School Operational Funds Accountability Through the School Activity and Budget Plan Application - Tri Prasetyo Handayani; Nur Khoiri; Ghufron Abdullah (BASICA, 2026)
This study aimed to analyze accountability in the management of School Operational Assistance Fund (BOSP) through the School Activity and Budget Plan Application (ARKAS) at St. Antonius 02 Elementary School in Semarang City. Using a qualitative single-case study design, purposive sampling was applied to select nine informants, including the principal, treasurer, asset officer, teachers, and school committee members. Data were collected through interviews, observation, and documentation to explore accountability practices in school financial management. The analysis focused on five accountability indicators: leadership responsibility, planning, control, accountability, and evaluation. The findings indicate that leadership responsibility was reflected in compliance with BOSP regulations and direct verification by the principal. Planning was conducted collaboratively through stakeholder deliberation based on actual school needs. Control was implemented through continuous supervision, transaction verification, and immediate clarification of inconsistencies. Accountability was demonstrated through systematic reporting, complete supporting documentation, and internal revision procedures before submission to the education office. Evaluation was carried out periodically through reflective review and corrective follow-up to improve subsequent budget implementation. These findings imply that accountability in BOSP management is strengthened when ARKAS is supported by disciplined internal control, active stakeholder participation, and systematic administrative practices. Overall, ARKAS contributed to more transparent, traceable, and accountable school financial governance, while providing practical implications for improving budget planning, supervision, reporting, and continuous evaluation in elementary school financial management.